Ultrawideband high‐gain dual‐polarized antenna with anti‐interference capability. Issue 9 (30th April 2019) - Le, Tuan Tu; Tran, Huy Hung
Abstract: In this article, a high‐gain dual‐polarized antenna with band‐rejection capability for ultrawideband (UWB) applications is proposed. Tapered dipoles are chosen as a primary radiator to achieve UWB operation and it is reflected by a metallic cavity reflector for high gain radiation. A notch at WLAN band is realized by etching a set of four bent slots in the radiating elements. The measured results demonstrate that the proposed design with overall dimensions of 0.69 λ L  × 0.69 λ L  × 0.16 λ L ( λ L is free‐space wavelength at the lowest operating frequency) has operating bandwidth of 95.1% (3.2‐9.0 GHz) and the rejected frequency band from 5.0 to 5.9 GHz. Additionally, good unidirectional radiation patterns with a broadside gain from 8.1 to 11.5 dBi and radiation efficiency of better than 90% are also achieved.